An Auxin-Responsive Promoter Is Differentially Induced by Auxin Gradients during Tropisms. - Li, Y (1991)
We constructed a chimeric gene consisting of a soybean small auxin up RNA (SAUR) promoter and leader sequence fused to an Escherichia coli [beta]-glucuronidase (GUS) open reading frame and a 3[prime] untranslated nopaline synthase sequence from Agrobacterium tumefaciens. This chimeric gene was used to transform tobacco by Agrobacterium-mediated transformation. In R2 etiolated transgenic tobacco seedlings, GUS expression occurred primarily in elongation regions of hypocotyls and roots. In green plants, GUS was expressed primarily in the epidermis and cortex of stems and petioles, as well as in elongation regions of anther filaments in developing flowers. GUS expression was responsive to exogenous auxin in the range of 10-8 to 10-3 M. During gravitropism and phototropism, the GUS activity became greater on the more rapidly elongating side of tobacco stems. Auxin transport inhibitors and other manipulations that blocked gravitropism also blocked the asymmetric distribution of GUS activity in gravistimulated stems. Light treatment of dark-grown seedlings resulted in a rapid decrease in GUS activity. Light-induced decay in GUS activity was fully reversed by application of auxin. Taken together, our results add support for the formation of an asymmetric distribution of auxin at sites of action during tropism.